Single-layer porous amorphous carbon film and preparation method thereof, and lithium ion battery modified diaphragm and preparation method thereof
By using a single-layer multi-layer multi-layer polyiteric amorphous carbon membrane modified diaphragm prepared by organic small molecules through Lange Mimore-thermal solution method, it solves the unevenness of the diameter of the lithium-ion battery and the growth of lithium branch crystals. The problem realizes the cycle stability and safety of lithium ion batteries.
Patent Information
- Application Number
- CN202411440385.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-16
AI Technical Summary
It is difficult to prepare high-quality large-area single-layer nanopore amorphous carbon films with high quality, and the membrane pore size range of lithium-ion batteries is large and unevenly distributed, resulting in uneven growth of lithium dendrites and attenuation of battery circulation performance.
A large-area single-layer porous amorphous carbon film was prepared using a "bottom-up" Langmuir film-forming and pyrolysis two-step method of organic small molecules, and was used in the preparation of modified separators for lithium-ion batteries to regulate Li+ Deposits and inhibits the growth of lithium dendrites.
Successfully prepared a single -layer multi -laminar non -crystal carbon film with good mechanical support and uniform nano -hole distribution, improved the cycle stability of lithium -ion batteries, suppressed the growth of lithium branches, and improved the safety of the battery.
Smart Images

Figure CN119349546A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of functional materials, and relates to porous amorphous carbon film materials, and specifically to a single-layer porous amorphous carbon film and a preparation method thereof, and a lithium-ion battery modified diaphragm and a preparation method thereof. Background Art
[0002] Carbon is one of the most versatile elements in the periodic table. It can react with almost all elements in the form of sp, sp 2 and sp 3 Hybridization is combined. Two-dimensional (2D) carbon materials composed of conjugated network structures have unique π-electron systems and special carrier transport properties. We can adjust the physical and chemical properties of 2D carbon materials, especially the band gap, by changing the periodicity of the hybridized carbon atom network. These 2D carbon materials have a wide range of applications in transistors, energy storage devices, and superconductors.
[0003] Many two-dimensional material membranes, such as graphene, do not have nanopores themselves. Nanopores can be introduced into two-dimensional material membranes through physical methods such as electron beam irradiation, plasma etching and ion bombardment. The disadvantage is that not only the chemical function of the pores is poorly controlled, but the scalability of the process remains elusive and the process cost is high. Although the bottom-up preparation of two-dimensional nanoporous membranes can solve these problems, it is still technically challenging due to the lack of reliable methods to produce high-quality large nanoporous two-dimensional membranes.
[0004] At present, the preparation of single-layer nanoporous amorphous carbon film is difficult. First, there is a contradiction between the amount of carbon source and the number of growth cores in the growth of single-layer amorphous carbon film. According to the Arrhenius equation, the growth of single-layer amorphous carbon film requires as many growth nucleation cores as possible. The method for preparing amorphous carbon film reported in the existing literature is mainly chemical vapor deposition. In the chemical vapor deposition method, the growth nucleation core requirement can usually be met by providing a large amount of carbon source (for example, increasing the methane flow rate and proportion), but at the same time, a large amount of carbon source will accelerate the growth of the carbon film into a multilayer structure instead of staying in a single layer, and it is difficult to obtain a large-area single-layer amorphous carbon film by this method.
[0005] Langmuir-Blodgett (LB) film technology is a single-molecule film deposition technology invented by Langmuir and Blodgett. The so-called LB film refers to a single-layer or multi-layer molecular film obtained by depositing one or more layers of molecular films spread on the surface of a certain liquid onto a certain substrate through a certain pulling method. Compared with other systems, LB film has many advantages: (1) ultra-thin and accurately controlled thickness, the film thickness is nanometer thickness; (2) the molecular arrangement in the film is highly ordered and anisotropic, which can be controlled at the molecular level, so that it can be designed and realized according to needs. Organization at the molecular level; (3) The film preparation conditions are mild and the operation is simple.
[0006] Lithium metal has a very high theoretical energy density (3860 mAh g -1 ), the lowest electrochemical redox potential (-3.04 V relative to standard hydrogen electrode) and the lowest density (0.534 g cm -3 ), is considered to be the ultimate material that can replace graphite negative electrodes in high energy density batteries. However, despite the many advantages of lithium metal batteries, their application still faces some problems: due to the continuous side reactions between the highly reactive metallic lithium and the organic electrolyte during the battery cycle, the Coulombic efficiency (CE) decreases. In addition, during the battery cycle, the uneven lithium precipitation on the surface of the metallic lithium negative electrode is prone to form needle-shaped, mossy or branch-like lithium dendrites. The continuous growth of lithium dendrites will cause repeated rupture and growth of the solid electrolyte interphase (SEI), resulting in the attenuation of the battery cycle performance, further piercing the diaphragm to reach the positive electrode, causing an internal short circuit, and ultimately causing the battery to catch fire and explode, posing a huge safety hazard.
[0007] In liquid-based lithium metal batteries, the separator is a key component. On the one hand, it acts as a barrier to isolate the positive and negative electrodes and prevent electron tunneling between the electrodes and internal short circuits. On the other hand, it also acts as a Li-ion battery between the positive and negative electrodes. + The diaphragm affects the mass transfer (diffusion) of lithium ions on the electrode, thereby affecting the growth of lithium dendrites. However, the role of the diaphragm in the growth of lithium dendrites has not received much attention. Currently, polyolefin diaphragms are more commonly used, but the pore size range of this diaphragm is large and the distribution is uneven, so uneven Li formation will occur during the lithium deposition process. + flux, it is precisely because of the uneven Li + The flux distribution caused the local excessive growth of lithium dendrites and the uneven deposition of lithium. + To solve the problem of uneven distribution, the development of advanced separators with uniform pore distribution or coatings with special structural arrangements can promote the formation of uniform Li + flux, thereby achieving excellent deposition cycle stability of the metallic lithium anode.
[0008] The work on membrane modification to inhibit lithium dendrites has mainly focused on using materials such as graphene, h-BN, and ceramic membranes to coat the surface of commercial membranes. However, these materials are highly polycrystalline and have many grain boundaries, which are mechanically weak points and may ultimately contribute to the growth of lithium dendrites. The ideal membrane must be designed to achieve Li + The uniform distribution of Li +flux, preventing the formation of a negative electrode nucleus of lithium metal with a thermodynamic radius higher than the critical thermodynamic radius. At the same time, the thickness of the diaphragm is also an influencing factor. When the thickness of the diaphragm is thicker, it will increase the Li + Resistance to flow. Summary of the invention
[0009] In view of the shortcomings of the prior art, the present invention aims to provide a single-layer porous amorphous carbon film and a preparation method, a lithium-ion battery modified diaphragm and a preparation method, and a large-area single-layer porous amorphous carbon film is prepared by a two-step method of Langmuir film formation-pyrolysis from organic small molecules "bottom-up", which effectively reduces the amount of carbon source and thus regulates the film thickness. The single-layer porous amorphous carbon film is used to prepare a lithium-ion battery modified diaphragm, which can effectively regulate Li + deposition and inhibit the growth of lithium dendrites.
[0010] In order to achieve the above object, the present invention adopts the following technical solutions:
[0011] A method for preparing a single-layer porous amorphous carbon film comprises the following steps:
[0012] Step 1, preparing the amphiphilic condensed ring aromatic monomer Tpy-large;
[0013] Step 2: Dissolve the amphiphilic condensed aromatic monomer Tpy-large prepared in step 1 in chloroform to make a 1 mg / L solution, and drip 20 uL of the solution onto a 50 cm 2 The water-air interface;
[0014] Step 3: After the chloroform is completely volatilized, the baffle of the Langmuir film preparation instrument is slowly pushed to maintain the interface assembly film of the polycyclic aromatic hydrocarbon molecules at an interface pressure of 5 to 20 mN / m, and the assembled film is transferred to the substrate by a vertical deposition method;
[0015] Step 4: Transfer the substrate with the assembled film prepared in step 3 to a rapid thermal processing tube furnace, and pyrolyze it at 800-900° C. in an argon atmosphere at normal pressure for 1 min to obtain a single-layer porous amorphous carbon film.
[0016] Preferably, the preparation method of the amphiphilic condensed aromatic hydrocarbon monomer Tpy-large described in step 1 comprises:
[0017] S1. Under nitrogen atmosphere, 26.7 g of hexaphenylbenzene was dissolved in 250 mL of 0.1 M sodium carbonate solution, and 40 mL of liquid bromine was added dropwise thereto while stirring. The mixture was stirred at room temperature overnight. The resulting precipitate was filtered and washed with 10% sodium bicarbonate to obtain hexaphenylbenzene bromide, which was recorded as substance 2.
[0018] S2, add 500 mg of 4'-(4-bromobenzene)-2,2':6',2"-isopyridine to 20 mL of acetic acid solution containing 365 mg of ammonium acetate, stir and react for 8 hours, filter the precipitate obtained by the reaction and recrystallize it in ethanol, dissolve the recrystallized product and 32 mg of Pd(dppf)Cl2, 379 mg of potassium acetate and 344 mg of biboric acid pinacol ester in 5 mL of DMSO, perform three cycles of freezing and deoxygenation, heat to 80 ° C and react for 12 hours under nitrogen protection, extract the reaction solution with chloroform after completion of the reaction, dry the extract with magnesium sulfate and evaporate the solvent, and recrystallize the obtained solid in ethanol to obtain pure substance 3;
[0019] S3. Substance 2 and substance 3 are subjected to classic Suzuki coupling to obtain the amphiphilic condensed ring aromatic hydrocarbon monomer Tpy-large.
[0020] Preferably, the waiting time for the chloroform described in step 3 to completely volatilize is 5 to 15 minutes.
[0021] Preferably, the substrate described in step three comprises a copper sheet, a silicon sheet or a glass sheet.
[0022] A single-layer porous amorphous carbon film prepared by the method as described above.
[0023] A method for preparing a modified lithium ion battery diaphragm comprises the following steps:
[0024] Step 1: transferring the single-layer porous amorphous carbon film according to claim 4 to a hydrophilic single-layer polypropylene separator by a PMMA method;
[0025] Step 2: The single-layer porous amorphous carbon film prepared in step 1 is transferred to a hydrophilic single-layer polypropylene separator by immersion washing with acetone for 10 minutes to remove polymethyl methacrylate and obtain a modified separator for a lithium-ion battery.
[0026] A modified lithium ion battery diaphragm prepared by the method as described above.
[0027] Compared with the prior art, the present invention has the following technical effects:
[0028] The present invention proposes for the first time a method of preparing a large-area single-layer porous amorphous carbon film from organic small molecules "bottom-up" by a two-step Langmuir film-forming-pyrolysis method, that is, a method of preparing an amorphous carbon film by using Tpy-large condensed-ring aromatic hydrocarbons as monomers, adopting the Langmuir film-forming method to assemble the film at the water-air interface and transferring pyrolysis. This method can solve the contradiction between the amount of carbon source and the number of growth cores mentioned above. Each condensed-ring aromatic hydrocarbon molecule is a nucleation core. The low volatility of condensed-ring aromatic hydrocarbon molecules also ensures that there are sufficient carbon source molecules during the film growth process, and a single-layer porous amorphous carbon film is successfully prepared; at the same time, the Langmuir film preparation technology can reasonably control the interface pressure, adjust the distance between amphiphilic condensed-ring aromatic hydrocarbon molecules, further reduce the amount of carbon source, and then control the film thickness; the amorphous carbon film has good mechanical support, and the amorphous carbon film itself has nanopores, which is a porous amorphous carbon film, and the surface of the film is evenly distributed with Li + Nanopores through which
[0029] The present invention combines a porous amorphous carbon film prepared by the Langmuir film-forming-pyrolysis method with a hydrophilic single-layer polypropylene diaphragm to prepare a lithium-ion battery modified diaphragm. Compared with the unmodified diaphragm, the diaphragm modified by the amorphous carbon film can regulate the Li + concentration distribution, improve the deposition behavior of lithium, and thus regulate the Li + The transfer and deposition of lithium metal batteries can inhibit the growth of lithium dendrites, providing a feasible and effective way to improve the cycle stability of lithium metal batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a schematic diagram of the preparation process of amphiphilic condensed ring aromatics;
[0031] Figure 2 Schematic diagram of the process of preparing a single-layer porous amorphous carbon film from amphiphilic condensed aromatic hydrocarbons;
[0032] Figure 3 This is a SEM image (10.0 μm) of the single-layer porous amorphous carbon film prepared in Example 1;
[0033] Figure 4 This is a SEM image (100.0 μm) of the single-layer porous amorphous carbon film prepared in Example 1;
[0034] Figure 5 The single-layer porous amorphous carbon film transferred onto the silicon wafer in Example 1 (dark color);
[0035] Figure 6 This is a test diagram for ion transmembrane transport;
[0036] Figure 7 Comparison of time-voltage curves of Li|Li symmetric batteries (0.5 mA cm -2; 1mAh cm -2 );
[0037] Figure 8 This is a comparison chart of LiFePO4|Li battery rate performance. DETAILED DESCRIPTION
[0038] The specific contents of the present invention are further explained in detail below in conjunction with embodiments.
[0039] Example 1
[0040] This embodiment provides a method for preparing a single-layer porous amorphous carbon film, comprising the following steps:
[0041] Step 1, preparing the amphiphilic condensed ring aromatic monomer Tpy-large;
[0042] S1. Under nitrogen atmosphere, 26.7 g of hexaphenylbenzene was dissolved in 250 mL of 0.1 M sodium carbonate solution, and 40 mL of liquid bromine was added dropwise thereto while stirring. The mixture was stirred at room temperature overnight. The resulting precipitate was filtered and washed with 10% sodium bicarbonate to obtain hexaphenylbenzene bromide, which was recorded as substance 2.
[0043] S2, add 500 mg of 4'-(4-bromobenzene)-2,2':6',2"-isopyridine to 20 mL of acetic acid solution containing 365 mg of ammonium acetate, stir and react for 8 hours, filter the precipitate obtained by the reaction and recrystallize it in ethanol, dissolve the recrystallized product and 32 mg of Pd(dppf)Cl2, 379 mg of potassium acetate and 344 mg of biboric acid pinacol ester in 5 mL of DMSO, perform three cycles of freezing and deoxygenation, heat to 80 ° C and react for 12 hours under nitrogen protection, extract the reaction solution with chloroform after completion of the reaction, dry the extract with magnesium sulfate and evaporate the solvent, and recrystallize the obtained solid in ethanol to obtain pure substance 3;
[0044] S3, obtaining the amphiphilic condensed aromatic monomer Tpy-large by using the classic Suzuki coupling of substance 2 and substance 3;
[0045] Step 2: Dissolve the amphiphilic condensed aromatic monomer Tpy-large prepared in step 1 in chloroform to make a 1 mg / L solution, and drip 20 uL of the solution onto a 50 cm 2 The water-air interface;
[0046] Step 3: After waiting for 15 minutes for the chloroform to completely evaporate, the baffle of the Langmuir film preparation instrument is slowly pushed to maintain the interface assembly film of the polycyclic aromatic hydrocarbon molecules at an interface pressure of 20 mN / m, and the assembled film is transferred to the silicon wafer substrate by a vertical deposition method;
[0047] Step 4: Transfer the substrate with the assembled film prepared in step 3 to a rapid thermal processing tube furnace, and pyrolyze it at 900° C. in an argon atmosphere and normal pressure for 1 min to obtain a single-layer porous amorphous carbon film.
[0048] The monolayer amorphous carbon film was transferred onto a SiN chip with a 500 nm diameter opening by the PMMA method, and the chip was placed in a dual-chamber flow cell, and LiCl solution or KCl solution (concentrations varied from 1 M to 1 mM) was placed on both sides. + or K + and Cl - The volume mobility of the ions is similar and the liquid junction potential can be ignored. Test the current value at different voltages and calculate its resistance.
[0049] A method for preparing a modified lithium ion battery diaphragm comprises the following steps:
[0050] Step 1: treating a single-layer polypropylene membrane with oxygen plasma for 5 seconds to obtain a hydrophilic surface, and transferring the single-layer porous amorphous carbon film according to claim 4 to the hydrophilic single-layer polypropylene membrane by a PMMA method;
[0051] The specific steps of the PMMA method include: applying 950PMMAA4 solution (PMMA is polymethyl methacrylate) on the surface of the amorphous carbon film with a substrate through a coating machine, and then immersing the substrate in an etching solution after drying. The etching solution is selected according to the selected substrate and can be a strong base, a strong acid, or a strong oxidant. After the substrate is completely dissolved, the film floating on the surface of the solution is washed three times with deionized water;
[0052] Step 2: The single-layer porous amorphous carbon film prepared in step 1 is transferred to a hydrophilic single-layer polypropylene membrane by immersion washing with acetone for 10 minutes, and the polymethyl methacrylate protective layer is removed to obtain a lithium-ion battery modified membrane.
[0053] In an argon-filled glove box (O2 < 0.1 ppm, H2O < 0.1 ppm), a 2032-type button cell shell was used, and an amorphous carbon film-modified diaphragm and Celgard2325 were used as diaphragms to assemble lithium symmetric cells, lithium-copper batteries, and lithium metal full cells, and the corresponding electrochemical tests were performed. In order to observe the morphology of lithium deposition on copper foil and the Coulomb efficiency test, copper foil was used as the working electrode in the lithium-copper battery. For the LiFePO4 full cell, the preparation process of the electrode sheet was as follows: battery-grade LiFePO4 was mixed with conductive carbon and polyvinylidene fluoride binder in a weight ratio of 70:20:10 with N-methyl-2-pyrrolidone solvent. The obtained slurry was coated on aluminum foil and vacuum dried at 90°C for 12 hours. 60 μL of 1MLiPF6, EC / DEC (volume ratio 1:1) electrolyte was added to the lithium symmetric battery and lithium-copper battery.
[0054] Figure 1 This is a schematic diagram of the preparation process of amphiphilic condensed ring aromatics;
[0055] Figure 2 Schematic diagram of the process of preparing a single-layer porous amorphous carbon film from amphiphilic condensed aromatic hydrocarbons;
[0056] Figure 3 This is a SEM image (10.0 μm) of the single-layer porous amorphous carbon film prepared in Example 1; Figure 4 The SEM image (100.0 μm) of the single-layer porous amorphous carbon film prepared in Example 1; Figure 3 and Figure 4 It can be seen that the membrane can be stably laid flat on the porous substrate and has good mechanical support;
[0057] Figure 5 A single layer of porous amorphous carbon film transferred onto a silicon wafer in implementation 1 (dark color);
[0058] Figure 6 This is a test diagram of ion transmembrane transport of a porous amorphous carbon membrane prepared in Example 1. Figure 6 It can be seen that the membrane surface is uniformly distributed with nanopores through which Li+ can pass;
[0059] Figure 7 Comparison of time-voltage curves of Li|Li symmetric batteries (0.5 mA cm -2 ; 1mAh cm -2 ); Figure 8 This is a comparison chart of LiFePO4|Li battery rate performance. Figure 7 and Figure 8 It can be seen that compared with the unmodified diaphragm, the addition of the modified membrane can regulate the Li + The concentration distribution of lithium metal batteries can be improved by improving the deposition behavior of lithium, which can provide a feasible and effective way to improve the cycle stability of lithium metal batteries.
[0060] Example 2
[0061] This embodiment provides a method for preparing a single-layer porous amorphous carbon film, comprising the following steps:
[0062] Step 1, preparing the amphiphilic condensed ring aromatic monomer Tpy-large;
[0063] S1. Under nitrogen atmosphere, 26.7 g of hexaphenylbenzene was dissolved in 250 mL of 0.1 M sodium carbonate solution, and 40 mL of liquid bromine was added dropwise thereto while stirring. The mixture was stirred at room temperature overnight. The resulting precipitate was filtered and washed with 10% sodium bicarbonate to obtain hexaphenylbenzene bromide, which was recorded as substance 2.
[0064] S2, add 500 mg of 4'-(4-bromobenzene)-2,2':6',2"-isopyridine to 20 mL of acetic acid solution containing 365 mg of ammonium acetate, stir and react for 8 hours, filter the precipitate obtained by the reaction and recrystallize it in ethanol, dissolve the recrystallized product and 32 mg of Pd(dppf)Cl2, 379 mg of potassium acetate and 344 mg of biboric acid pinacol ester in 5 mL of DMSO, perform three cycles of freezing and deoxygenation, heat to 80 ° C and react for 12 hours under nitrogen protection, extract the reaction solution with chloroform after completion of the reaction, dry the extract with magnesium sulfate and evaporate the solvent, and recrystallize the obtained solid in ethanol to obtain pure substance 3;
[0065] S3, obtaining the amphiphilic condensed aromatic monomer Tpy-large by using the classic Suzuki coupling of substance 2 and substance 3;
[0066] Step 2: Dissolve the amphiphilic condensed aromatic monomer Tpy-large prepared in step 1 in chloroform to make a 1 mg / L solution, and drip 20 uL of the solution onto a 50 cm 2 The water-air interface;
[0067] Step 3: After waiting for 5 minutes for the chloroform to completely evaporate, the baffle of the Langmuir film preparation instrument is slowly pushed to maintain the interface assembly film of the polycyclic aromatic hydrocarbon molecules at an interface pressure of 5 mN / m, and the assembled film is transferred to the copper substrate by a vertical deposition method;
[0068] Step 4: Transfer the substrate with the assembled film prepared in step 3 to a rapid thermal processing tube furnace, and pyrolyze it at 800° C. in an argon atmosphere at normal pressure for 1 min to obtain a single-layer porous amorphous carbon film.
[0069] Example 3
[0070] This embodiment provides a method for preparing a single-layer porous amorphous carbon film, comprising the following steps:
[0071] Step 1, preparing the amphiphilic condensed ring aromatic monomer Tpy-large;
[0072] S1. Under nitrogen atmosphere, 26.7 g of hexaphenylbenzene was dissolved in 250 mL of 0.1 M sodium carbonate solution, and 40 mL of liquid bromine was added dropwise thereto while stirring. The mixture was stirred at room temperature overnight. The resulting precipitate was filtered and washed with 10% sodium bicarbonate to obtain hexaphenylbenzene bromide, which was recorded as substance 2.
[0073] S2, add 500 mg of 4'-(4-bromobenzene)-2,2':6',2"-isopyridine to 20 mL of acetic acid solution containing 365 mg of ammonium acetate, stir and react for 8 hours, filter the precipitate obtained by the reaction and recrystallize it in ethanol, dissolve the recrystallized product and 32 mg of Pd(dppf)Cl2, 379 mg of potassium acetate and 344 mg of biboric acid pinacol ester in 5 mL of DMSO, perform three cycles of freezing and deoxygenation, heat to 80 ° C and react for 12 hours under nitrogen protection, extract the reaction solution with chloroform after completion of the reaction, dry the extract with magnesium sulfate and evaporate the solvent, and recrystallize the obtained solid in ethanol to obtain pure substance 3;
[0074] S3, obtaining the amphiphilic condensed aromatic monomer Tpy-large by using the classic Suzuki coupling of substance 2 and substance 3;
[0075] Step 2: Dissolve the amphiphilic condensed aromatic monomer Tpy-large prepared in step 1 in chloroform to make a 1 mg / L solution, and drip 20 uL of the solution onto a 50 cm 2 The water-air interface;
[0076] Step 3: After waiting for 10 minutes for the chloroform to completely evaporate, slowly push the baffle of the Langmuir film preparation instrument to maintain the interface assembly film of the polycyclic aromatic hydrocarbon molecules at an interface pressure of 15 mN / m, and transfer the assembled film to the glass substrate by a vertical deposition method;
[0077] Step 4: Transfer the substrate with the assembled film prepared in step 3 to a rapid thermal processing tube furnace, and pyrolyze it at 850° C. in an argon atmosphere at normal pressure for 1 min to obtain a single-layer porous amorphous carbon film.
[0078] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, a person skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the present invention.
Claims
1. A method for preparing a single-layer porous amorphous carbon film, characterized in that: The following steps are involved: Step 1, preparing the amphiphilic condensed ring aromatic hydrocarbon monomer Tpy-large; Step 2: Dissolve the amphiphilic condensed aromatic monomer Tpy-large prepared in step 1 in chloroform to make a 1 mg / L solution, and drop 20 uL of the solution onto a 50 cm 2 The water-air interface; Step 3: After the chloroform is completely volatilized, the baffle of the Langmuir film preparation instrument is slowly pushed to maintain the interface assembly film of the polycyclic aromatic hydrocarbon molecules at an interface pressure of 5 to 20 mN / m, and the assembled film is transferred to the substrate by a vertical deposition method; Step 4: Transfer the substrate with the assembled film prepared in step 3 to a rapid thermal processing tube furnace, and pyrolyze it at 800-900° C. in an argon atmosphere at normal pressure for 1 min to obtain a single-layer porous amorphous carbon film.
2. The method for preparing a single-layer porous amorphous carbon film according to claim 1, characterized in that: The preparation method of the amphiphilic condensed ring aromatic hydrocarbon monomer Tpy-large described in step 1 comprises: S1. Under nitrogen atmosphere, 26.7 g of hexaphenylbenzene was dissolved in 250 mL of 0.1 M sodium carbonate solution, and 40 mL of liquid bromine was added dropwise thereto while stirring. The mixture was stirred at room temperature overnight. The resulting precipitate was filtered and washed with 10% sodium bicarbonate to obtain hexaphenylbenzene bromide, which was recorded as substance 2. S2, add 500 mg of 4'-(4-bromobenzene)-2,2':6',2"-isopyridine to 20 mL of acetic acid solution containing 365 mg of ammonium acetate, stir and react for 8 hours, filter the precipitate obtained by the reaction and recrystallize it in ethanol, dissolve the recrystallized product and 32 mg of Pd(dppf)Cl2, 379 mg of potassium acetate and 344 mg of biboric acid pinacol ester in 5 mL of DMSO, perform three cycles of freezing and deoxygenation, heat to 80 ° C and react for 12 hours under nitrogen protection, extract the reaction solution with chloroform after completion of the reaction, dry the extract with magnesium sulfate and evaporate the solvent, and recrystallize the obtained solid in ethanol to obtain pure substance 3; S3. Substance 2 and substance 3 are subjected to classic Suzuki coupling to obtain the amphiphilic condensed ring aromatic hydrocarbon monomer Tpy-large.
3. The method for preparing a single-layer porous amorphous carbon film according to claim 1, characterized in that: The waiting time for the chloroform described in step 3 to completely evaporate is 5 to 15 minutes.
4. The method for preparing a single-layer porous amorphous carbon film according to claim 1, characterized in that: The substrate described in step three includes a copper sheet, a silicon sheet or a glass sheet.
5. A single-layer porous amorphous carbon film prepared by the method according to any one of claims 1 to 4.
6. A method for preparing a modified lithium ion battery diaphragm, characterized in that: The following steps are involved: Step 1: transferring the single-layer amorphous carbon film according to claim 5 to a hydrophilic single-layer polypropylene diaphragm by a PMMA method; Step 2: The single-layer amorphous carbon film prepared in step 1 is transferred to a hydrophilic single-layer polypropylene membrane by immersion washing with acetone for 10 minutes to remove polymethyl methacrylate and obtain a modified membrane for a lithium-ion battery.
7. A lithium ion battery modified diaphragm prepared by the method according to claim 6.
Citation Information
Patent Citations
Organic electroluminescent host material and application thereof in organic electroluminescent device
CN113121406A
Nano-thickness squaric acid MOF film and preparation method thereof
CN116272427A
Preparation method of single-layer amorphous fullerene film
CN116495723A
Lithium metal battery negative electrode, preparation method thereof and lithium metal battery
CN118572040A
Carbon matrix-and carbon matrix composite-based dendrite-Intercepting layer for alkali metal secondary battery
US20160344010A1